(untitled) (Proceedings of the International Conference on Public Health, 2022)
Results from previous research shows that high outdoor air temperature can be detrimental to thermal comfort, health and productivity. However, are the results applicable to building construction workers in Nigeria? In view of this question, this study investigated the effect of outdoor air temperature on the thermal comfort, health and performance of a sample of Sandcrete block layers at a building construction site in Abuja, Nigeria. The study involved literature review and a field experiment. The field experiment examined the thermal comfort, health and performance of a sample Sandcrete block layers at LT 28.50C and HT 37.010C. (LT) and (HT) are the lowest and highest naturally occurring outdoor air temperatures in the construction site during the study. Paired t-test and Wilcoxon-signed ranked test was used to analyse the data from the field experiment. Result from analysis of data shows that: the thermal comfort of the samples was significantly affected at HT 37.01 0C in comparison to LT 28.50C. Also core body temperature significantly increased at HT 37.010C in comparison LT 28.50C. Furthermore, sensation of skin burn, fatigue and negative mood significantly increased at HT 37.010C in comparison LT 28.50C. No significant change in symptoms of headache and dizziness was observed. Lastly, performance of the sandcrete block was slightly low at HT 37.010C in comparison to LT 28.50C. The conclusion from this study is that, high outdoor temperature (37.010C) is detrimental to the thermal comfort, health and performance sandcrete block layers in Nigeria. The result from this study complements the findings of another related research. Broadly, results from this study provides empirical data that may stimulate strategies of mitigating the effect of high outdoor air temperature on the thermal comfort, health and performance of workers during high outdoor temperatures at construction sites in Nigeria.